Diagnóstico do conhecimento de uma comunidade rural sobre os resíduos de equipamentos elétricos e eletrônicos - Guenther, Mariana; Silva, Danielle Nathally (Revista Brasileira de Educação Ambiental (RevBEA), 2025)
This study aimed to diagnose the knowledge of a rural community (Paudalho, PE, Brazil) about waste electrical and electronic equipment (WEEE), through interviews with various community stakeholders. The research results showed that although participants are aware of this type of waste and its environmental impact, few are aware of its health effects, which can pose serious risks, especially for workers who handle this material. Therefore, carrying out environmental education actions with the population is essential if the selective collection program is to be implemented efficiently and on a long-term basis.